Kerajaan Menurut Paulus dalam Dialog dan Nilai - nilai Adat Batak - Clawdya Tampubolon; Harjaya Situmeang; Tupa Pebrianti Lumbantoruan (Pusat Riset dan Inovasi Nasional, 2025)
This research examines the interaction between Paul's understanding of the Kingdom of God and Batak cultural values, especially in the social and spiritual aspects of Batak society. Paul taught that the Kingdom of God is not just a hope for the future, but a reality that is present in the lives of believers through righteousness, peace and joy. present in the lives of believers through righteousness, peace, and joy by the Holy Spirit. by the Holy Spirit. Meanwhile, Batak culture is shaped by principles such as Dalihan Na Tolu, the spirit of gotong royong (marsiadapari), and respect for ancestors, which form the basis of their social and ethical order. their social and ethical order. This research uses a literature study with a theological approach theological approach to examine the harmony and potential tensions between Paul's teachings and Batak customs. and Batak customs. The results of the analysis show that the encounter between the two can create a mutually enriching integration, where Batak customs can be given new meaning by the values of the gospel without losing the meaning of the gospel. given new meaning by gospel values without losing its cultural identity. Practically speaking, this dialogue encourages Batak Christians to apply the values of love, justice and service in the context of the Gospel. love, justice, and service in their cultural context, so that the Kingdom of God can be realised in everyday life that is relevant and down to earth. and down to earth.